(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: With around 31% mortality, cardiovascular diseases continue to be the major cause of death. Heart failure can be predicted early by evaluating risk factors such as hypertension, diabetes, obesity, and hypercholesterolemia. The predictors range from old age as a mild risk predictor to coronary artery syndrome as the major one. Methodology: Studies were searched on electronic database such as Google scholar and PubMed. Patient data was extracted from the chosen studies. Study specifics (e.g., author, publication year, study design), Patient traits, including sample size, demographics, and clinical presentation, Identification of cardiac risk factors (using, for example, biomarkers, imaging methods, and clinical assessments) were extracted from the studies. Results: Only full text articles that included risk stratification through Charlson comorbidity index (CCI) were included in the study. The result indicated that a higher CCI score will mean a negative outcome is predicted. The hazard ratio was stronger when adjusted for comorbid. Conclusion: The quantitative impact of early detection of cardiac risk on the success rate of cardiac interventions is profound, underlining the critical need for public health initiatives promoting early screening and lifestyle modifications.